Terapi Saat Ini untuk Chronic Inflammatory Demyelinating Polyradiculoneuropathy (CIDP): Sebuah Literature Review - Hunaifi, Ilsa Hunaifi; Wicaksono, Teguh Budi; Nugraha, Gede Rama Hardy; Maulida, Rizka Ayu; Kusumadewi, Rima Cahyati; Pratiwi, Rukmanggana Satya; Amaliya, Annisa Risqi; Sepestian, Ghina Shadrina Rienti (LPPM Universitas Mataram, 2024)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an autoimmune disease. The European Academy of Neurology recommends treatment using corticosteroids, immunoglobulin, plasma exchange, & other treatments as treatment options for chronic inflammatory demyelinating polyradiculoneuropathy. However, several studies in recent years have shown that there is potential in the treatment of chronic inflammatory demyelinating Polyradiculoneuropathy. The aim of this literature review is to provide the latest therapy for chronic inflammatory demyelinating polyradiculoneuropathy based on guidelines as well as other information therapy alternatives. The method used in this literature review uses searches in several databases. The results of several studies show the development of chronic inflammatory demyelinating polyradiculoneuropathy therapy both pharmacologically & non-pharmacologically. The development of therapy for chronic inflammatory demyelinating polyradiculoneuropathy, namely hematopoietic stem cells & spinal cord stimulation, shows potential as a therapeutic option for patients with chronic inflammatory demyelinating polyradiculoneuropathy.